Keanekaragaman Vegetasi Hutan Mangrove di Pulau Payung Sungsang Banyuasin Sumatera Selatan - Asia Afriyani; Fauziyah Fauziyah; Mazidah Mazidah; Ratih Wijayanti (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2017)
Afriyani et al, 2017. Vegetation Diversity of Mangrove Forest in Payung island Sungsang Village Banyuasin District. JLSO 6(2):113-119.The mangrove forest is a natural biological resources with various diversity potential that provides benefits directly or indirectly for the life of living beings. Payung island, Sungsang Village, Banyuasin District is one of the areas in South Sumatra Province where the forest mangrove still well preserved. The research abaout mangrove diversity has been conducted in Payung Island inÂ November 2017, The aim of this research was to know the composition and species diversity of mangrove in the island. The collection of primary data in this research was included measurements of the distribution of mangrove vegetation. Important Value index (IVI) is a diversity index and parameter analysis of mangrove vegetation. There are 4 species of mangrove was founded in 3 transect observations, namely Avicennia alba, Avicennia marina, Bruguera apicullata gymnorhiza and Rhizophora. Bruguera vegetation dominate gymnorhiza tree level, while at the level of the child dominated two types of mangrove vegetation i.e. vegetation Avicennia marina and Rhizophora apicullata vegetation. The condition of mangrove forestÂ showed that community in Payung Island are stable that It contains mangrove forest condition criteria Broken-with the value of the density of Mangrove (ind/ha) < 1000.